Predictors of Glycated Hemoglobin among Jordanian Diabetic Patients - Sawsan HAMMAD; Muhammad DARAWAD; Eman HOURANI; Waddah DEMEH (Tehran University of Medical Sciences, 2015)
Background: We explored the level of Jordanian patients' knowledge, diabetes related distress, self-management activities and these effects on the A1C level. Methodology: This descriptive cross-sectional correlational design (conducted in 2013) was utilized to recruit 289 diabetic patients from outpatient diabetes clinics, using self-reported questionnaires (Diabetes Knowledge Test, Diabetes Distress Scale, and Diabetes Self-Management Questionnaire) in addition to chart review for selected variables. Results: Participants' had mean glycated hemoglobin of 7.88%. Good glycemic control was significantly associated with higher self-management activities (r= -.147), high income (r= -.171), older age (r= -.252), shorter duration of illness (r= .153), and low levels of distress. Despite these relationships only age, duration of illness and income significantly predicted A1C (F (5, 284) = 11.57, P<.001, R2 = .17). Further, diabetes knowledge, diabetes-related distress, and self-management could not predict A1C level. Conclusion: Only diabetes-related distress and self-management correlated with patients' A1C, with no predictive power. Thus, further research is required to shed the light on the large unexplained components of the A1C variance.   Keywords: Glycated hemoglobin, Diabetes related distress, Self-management, Diabetes